2010
DOI: 10.1038/nature09523
|View full text |Cite
|
Sign up to set email alerts
|

The CRISPR/Cas bacterial immune system cleaves bacteriophage and plasmid DNA

Abstract: Bacteria and Archaea have developed several defence strategies against foreign nucleic acids such as viral genomes and plasmids. Among them, clustered regularly interspaced short palindromic repeats (CRISPR) loci together with cas (CRISPR-associated) genes form the CRISPR/Cas immune system, which involves partially palindromic repeats separated by short stretches of DNA called spacers, acquired from extrachromosomal elements. It was recently demonstrated that these variable loci can incorporate spacers from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
1,513
2
30

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 1,998 publications
(1,659 citation statements)
references
References 37 publications
33
1,513
2
30
Order By: Relevance
“…Recent research, first described in 2002, has demonstrated the importance of a novel adaptive mechanism that provides bacteria immunity to phage 7,8 , that is based on clustered regularly interspaced short palindromic repeats (CRISPR) loci and their associated genes (cas) [9][10][11] . CRISPR-Cas immunity involves a multistep process that begins with the acquisition of short, exogenous nucleic acid fragments called spacers.…”
mentioning
confidence: 99%
“…Recent research, first described in 2002, has demonstrated the importance of a novel adaptive mechanism that provides bacteria immunity to phage 7,8 , that is based on clustered regularly interspaced short palindromic repeats (CRISPR) loci and their associated genes (cas) [9][10][11] . CRISPR-Cas immunity involves a multistep process that begins with the acquisition of short, exogenous nucleic acid fragments called spacers.…”
mentioning
confidence: 99%
“…Although it was proposed that the PAM motif recognized by the CRISPR-Cas system, which was initially used to recognize protospacers for spacer insertion, is the marker which the complex uses to identify foreign DNA, it has been shown in E. coli that only 6 of the 7 nucleotides of the PAM need to be matched to the crRNA for the effector complex to cleave the DNA [117]. The complex might rely on Csn1 (Cas5) in order to cleave the foreign DNA after it is recognized [51].…”
Section: Invader Silencingmentioning
confidence: 99%
“…[1][2][3] Therefore, its potential is being explored in the research for treatment of human diseases such as sickle cell anemia, 4) hemophilia, 5,6) and human immunodeficiency virus (HIV) infection. 7) Liver diseases have been also regarded as targets of genome editing applications because of the variety of serious inherited and acquired genetic disorders caused by mutations in single genes.…”
mentioning
confidence: 99%